Measuring dispersion of settlements - Borko, Sebastijan; Drozg, Vladimir (Journal for Geography, 2011)
The change in the settlement pattern is usually shown using qualitative labels, which is often not accurate enough. The article presents a method of displaying the dispersion of the settlement pattern with numerical indicators. It is based on a Swiss study and is based on the geometry of the space, or on the weighted distances between built-up areas. The method provides insight into regional and temporal changes in the settlement pattern. The most important realization of the used display is that the dispersion of the cause of settlement in the considered settlements increased significantly between the years 1860 and 2010.
Keywords: dispersal settlement pattern; mesures of dispersion; sprawl; Slovenia